Application of Electronic Learning by Utilizing Virtual Reality (VR) and Augmented Reality (AR) Methods in Natural Sciences Subjects (IPA) in Elementary School Students Grade 3 - Anggara, Risan Putra; Musa, Purnawarman; Sri Lestari; Widodo, Suryarini (JTP - Jurnal Teknologi Pendidikan, 2021)
Corona Virus Disease 2019 (Covid-19) has stopped all aspects of human life, including the world of education. The Ministry of Education of the Republic of Indonesia has stopped face-to-face teaching and learning activities in schools, replacing them with online methods. Work from Home (WFH) is an adaptation of activities as applied online methods to anticipate learning activities during the Covid-19 Pandemic. Learning based on digital transformation technology utilizes network technology entirely online. The application of e-learning technology in the teaching and learning process is a choice for various educational institutions. The use of technology can maximize students ’learning time efficiency and increase students’ concentration. Learning with the Virtual Reality (VR) method directs students to discoveries, motivates, encourages, and provides more curiosity for students in learning. Besides VR, Augmented Reality (AR) is a learning method for students to interact with virtual objects and real objects. The author proposes e-learning based learning in Natural Sciences (IPA) subjects in grade 3 in Elementary Schools. The research proposal develops lessons using a virtual approach from real events and provides phenomena of natural occurrences. Science lessons in Elementary Schools increase the curiosity of students scientifically. This method will help students develop the ability to ask questions and find answers to natural phenomena. The research stages carried out in application development are analysis, design, implementation, and application testing. The test results by adding e-learning to traditional learning methods impacted students’ understanding of the material with an increased level of understanding by 24%.